Report on the coins presented to the Society from the Honourable the Lords Commissioners of Her Majesty's Treasury (Proceedings of the Society of Antiquaries of Scotland, 1855)
An account of the Medieval and Roman coins in the Society's collections, including the king or emperor depicted on each coin and their scarcity.